2021
DOI: 10.3389/fphar.2021.794458
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Ameliorates Aβ-Induced Memory Deficits and Neuronal Atrophy via Inhibition of PDE2 and PDE4

Abstract: Inhibition of phosphodiesterase 2 and 4 (PDE2A and PDE4) increases the intracellular cAMP and/or cGMP levels, which may prevent Amyloid β 42 oligomers (Aβ) related cognitive impairment and dementias. Baicalein, one of natural flavones found in the root of Scutellaria baicalensis Georgi, has a wide range of pharmacological activities including antioxidant and anti-inflammatory effects. However, no studies suggest whether baicalein mediated anti-Alzheimer’s disease (AD) events involve PDEs subtypes-mediated neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
3
9
0
1
Order By: Relevance
“…Similarly, previous studies have demonstrated that baicalein protects against amyloidβ induced neuronal cell lesions, both in vitro and in vivo (Gasiorowski et al, 2012;Yu et al, 2012;Shi et al, 2021;Wong et al, 2014. These findings support the Aβ ameliorating effect of baicalein. The study conducted by Shi et al (2021) also corroborates the results of the present research.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similarly, previous studies have demonstrated that baicalein protects against amyloidβ induced neuronal cell lesions, both in vitro and in vivo (Gasiorowski et al, 2012;Yu et al, 2012;Shi et al, 2021;Wong et al, 2014. These findings support the Aβ ameliorating effect of baicalein. The study conducted by Shi et al (2021) also corroborates the results of the present research.…”
Section: Discussionsupporting
confidence: 83%
“…The combination of baicalein and memantine enhanced BDNF expression in the hippocampus and cortex. In 2021, Shi et al found similar results, with improved BDNF expression regulating PDE2A/PDE4dependent neuroprotective pathways, which ultimately improve neuronal remodeling and cognitive function.…”
Section: Discussionmentioning
confidence: 61%
“…Evidence indicates that baicalein notably ameliorates behavioral and cognitive impairment in AD rats [ 38 ]. An experimental study has shown that baicalein improves A β -induced memory deficits and neuronal atrophy via inhibition of phosphodiesterase 2 (PDE2) and PDE4 [ 39 ]. Quercetin protects against the effects of harmful substances and has multiple beneficial effects in AD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Байкалейн обладает рядом важных для нейропротектора фармакологических свойств, а именно, снижает окислительный стресс, ингибирует агрегацию Аβ, стимулирует нейрогенез [197]. Байкалейн также предотвращает Aβ-индуцированную атрофию нейронов и улучшал память мышей [198]. Комбинация байкалейна и транс-халкона значи-тельно снижала уровни АФК и Aβ 1-42 в клетках дрожжей, экспрессирующих Aβ 1-42 , не влияя на их рост [199].…”
Section: потенциальные нейропротекторные препараты воздействующие одн...unclassified
“…Baicalein exhibits a number of important pharmacological properties as a neuroprotector: it reduces OS, inhibits Aβ aggregation, and stimulates neurogenesis [ 197 ]. Baicalein was also shown to prevent Aβ-induced neuronal atrophy and improve memory in mice [ 198 ]. The combination of baicalein and trans-chalcone significantly reduced the levels of ROS and Aβ 1-42 in yeast cells expressing Aβ 1-42 without affecting their growth in [ 199 ].…”
Section: Potential Neuroprotector Agents Acting On Both Aβ Deposition...mentioning
confidence: 99%